Chloride ion transport mechanism in concrete due to wetting and drying cycles. (June 2015) - Gang, Xu; Yun‐pan, Li; Yi‐biao, Su; Ke, Xu
Abstract The transport mechanism of chloride ions in concrete during wetting and drying cycles of varying duration is evaluated in this paper. The experimental test results were used to validate a numerical simulation model in order to assess the influence of diffusion coefficient, surface chloride ion concentration and ratio of dry‐wet cycle durations on the transport mechanism of chloride ions in concrete. Experimental and numerical analysis results indicate that the maximum transmission depth of chloride ions in concrete depends on the diffusion coefficient and the dry‐wet cycle regime but has little relationship with the surface concentration of chloride. The chloride ion transmission in the surface zone accelerates only if the dry‐wet ratio is > 1. As the dry‐wet ratio increases, so the chloride ion transmission accelerates. It tends to become stable when the dry‐wet ratio reaches 5:1. The dry‐wet cycles accelerate the transport process of chloride ions within a certain distance from the surface; beyond this distance, chloride ions in the complete immersion specimen migrate more rapidly than those under dry‐wet cycles. The peak concentration of chloride ions within the convection zone has a relationship with the diffusion coefficient, the surface chloride ion concentration and the dry‐wet regime. The smaller the diffusion coefficient, the higher the surface chloride concentration; the greater the dry‐wet ratio, the higher the peak of convection can be.